2012
DOI: 10.1080/09540121.2012.668166
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to involvement of men in ANC and VCT in Khayelitsha, South Africa

Abstract: We used qualitative methods to assess pregnant women and men's attitudes, feelings, beliefs, experiences and reactions to male partners’ involvement in antenatal clinic (ANC) in Khayelitsha, Cape Town, South Africa. The aims of these studies were to determine barriers to male partners’ attendance of ANC with their pregnant female partners and to identify possible strategies to overcome these barriers. Findings from the qualitative studies demonstrated that pregnant women were keen to invite their male sexual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 12 publications
(11 reference statements)
6
41
2
Order By: Relevance
“…Extending invites to men as expressed in other studies is also a way of promoting MI [20,23,53]. A review of literature concluded that MI requires a multimethod approach such as invitation letter accompanied by community education and mass media campaigns [78].…”
Section: Discussionmentioning
confidence: 99%
“…Extending invites to men as expressed in other studies is also a way of promoting MI [20,23,53]. A review of literature concluded that MI requires a multimethod approach such as invitation letter accompanied by community education and mass media campaigns [78].…”
Section: Discussionmentioning
confidence: 99%
“…Social norms can prevent women from asking their partners to attend ANC or for men to concede to attending [ 19 ]. ANC has been considered an arena for women, with predominately female staff, and reports of hostile reactions towards male partners if they attend [ 20 ]. Clinic opening hours and long waiting time conflict with male partner work commitments and, for some, the pressure to earn an income is greater than that of attending ANC [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANC has been considered an arena for women, with predominately female staff, and reports of hostile reactions towards male partners if they attend [ 20 ]. Clinic opening hours and long waiting time conflict with male partner work commitments and, for some, the pressure to earn an income is greater than that of attending ANC [ 20 , 21 ]. Formative research from different sub-Saharan African countries has recommended interventions to increase male partner attendance or involvement, such as opening clinics at evenings or weekends, peer-to-peer ANC/PMTCT education led by men, or home based CVCT during pregnancy [ 14 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All willing participants were asked to sign the consent form before interviews commenced. An interview guide created from similar studies served as a guide for the researcher during the interview process [4,59]. After the opening question, the interview guide was used flexibly.…”
Section: Data Collectionmentioning
confidence: 99%